Composite cured coating and preparation method thereof
By superimposing a composite cured coating of a first cured layer, a catalytic layer and a second cured layer on the substrate, the brittleness and line width problems of the ITO conductive glass substrate are solved, and a highly adhesive, strong and bendable conductive layer is achieved.
Patent Information
- Application Number
- CN202410414311.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-04-08
- Publication Date
- 2025-10-21
AI Technical Summary
In the prior art, electronic circuits made of ITO conductive glass substrates have the problems of high brittleness, inflexibility, and excessively wide line width, making it impossible to produce fine circuits.
A composite cured coating is used, including a first cured layer, a catalytic layer and a second cured layer stacked in sequence. The first cured layer is composed of a low-functional group polymer and an initiator, the catalytic layer is formed by a catalyst precursor, and the second cured layer is composed of a metal complex salt solution. The conductive layer is formed by curing through light or heat radiation.
The result is a cured layer with high adhesion, high strength and resistance to brittle cracks, good bending properties, and the ability to form a conductive pattern.
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of flexible touch screens, and in particular to a composite cured coating and a preparation method thereof. Background Art
[0002] In many industrial application fields, it is necessary to form a cured coating on the surface of the substrate, especially in the electronics field, such as printed circuit boards, flexible touch screens, electrodes of electronic sensors, and liquid crystal displays. Other fields such as radio frequency antennas, battery electrodes, smart cards, power supplies and battery contacts are also involved.
[0003] Traditional touch screens and electronic display technologies typically use ITO conductive glass as the substrate for circuit preparation. However, the use of ITO conductive glass to prepare electronic circuits has significant disadvantages and limitations, such as tight raw material supply, brittleness, inflexibility, and the inability to produce fine circuits due to the excessive width of the prepared circuits. Summary of the Invention
[0004] The purpose of the present invention is to solve the problem of high brittleness faced by the prior art by providing a composite cured coating and a preparation method thereof based on the defects of the prior art.
[0005] To solve the above problems, the present invention is achieved through the following technical solutions:
[0006] The present invention provides a composite solidified coating, which comprises a first solidified layer stacked sequentially on the surface of a substrate, a catalytic layer for initiating the formation of a second solidified layer, and the second solidified layer having a conductive effect; wherein: the first solidified layer is formed by coating a first liquid on the surface of the substrate and solidifying, and the first liquid comprises a low-functionality polymer that can undergo polymerization to form a cross-linked polymer, an initiator, and a first solvent; the catalytic layer is formed by coating a catalyst precursor liquid, a catalyst dispersion, or a catalyst ink on the first solidified layer and solidifying; the second solidified layer is obtained by forming a second liquid on the catalytic layer, and the second liquid is a metal complex salt solution, which comprises a metal salt, a complexing agent, a reducing agent, a stabilizer, a pH regulator, and water.
[0007] Furthermore, a composite cured coating: the first liquid comprises the following components by weight: 10.0-30.0 wt% of an acrylate monomer, 20.0-45.0 wt% of a low-functionality polymer, 1.0-5.0 wt% of an initiator, and 40.0-60.0 wt% of a first solvent; wherein the acrylate monomer is selected from one of methyl acrylate, ethyl acrylate, methyl 2-methacrylate, and ethyl 2-acrylate;
[0008] The low-functionality polymer is selected from at least one of monofunctional acrylate, difunctional acrylate, trifunctional acrylate, tetrafunctional acrylate, and hexafunctional acrylate; the monofunctional acrylate is selected from one of isobornyl acrylate SR506D, caprolactone acrylate SR495, and lauryl acrylate SR335; the difunctional acrylate is selected from one of tripropylene glycol diacrylate, dipropylene glycol diacrylate, and polyethylene glycol 400 diacrylate; the trifunctional acrylate is selected from one of trimethylolpropane triacrylate and ethoxylated trihydroxypropane triacrylate; the tetrafunctional acrylate is selected from one of ethoxylated pentaerythritol tetraacrylate and ditrimethylolpropane tetraacrylate; and the hexafunctional acrylate is selected from dipentaerythritol hexaacrylate;
[0009] The initiator is a UV photoinitiator or a thermal initiator, the UV photoinitiator is selected from one of Irgacure184, Irgacure369, Irgacure917, and Irgacure1700, and the thermal initiator is selected from one of benzoyl oxide, lauroyl peroxide, azobis-(1-hydroxycyclohexane), and AIBN; the first solvent is selected from one of acetone, cyclopentanone, cyclohexanone, ethyl lactate, and ethyl acetate.
[0010] Furthermore, a composite cured coating: the low-functional polymer is selected from at least one of trifunctional acrylate, tetrafunctional acrylate, and hexafunctional acrylate, and the trifunctional acrylate accounts for no more than 45% of the weight of the first liquid, the tetrafunctional acrylate accounts for no more than 25% of the weight of the first liquid, and the hexafunctional acrylate accounts for no more than 10% of the weight of the first liquid.
[0011] Furthermore, a composite cured coating: the catalyst precursor liquid includes the following components in mass fraction: 5.0-10.0 wt% of a precious metal salt, 5.0-10.0 wt% of a first dispersant, and the remainder a second solvent; wherein: the precious metal salt is selected from silver salt, palladium salt, platinum salt or gold salt; the first dispersant is polyvinylpyrrolidone and / or N-methylpyrrolidone; the second solvent is selected from at least one of ethylene glycol, glycerol, diacetone alcohol, methoxypropanol, and ethyl acetate.
[0012] Preferably, the noble metal salt can be an inorganic salt, such as palladium chloride, palladium nitrate, silver nitrate, etc.; it can also be an organic salt, such as palladium acetate, palladium propionate. Currently, the preferred organic salt is palladium acetate, and the inorganic salt is silver nitrate.
[0013] Furthermore, a composite curing coating: the catalyst dispersion comprises the following components by mass fraction: 0.2-0.5 wt% of a noble metal salt, 10.0-15.0 wt% of a third solvent, 1.0-5.0 wt% of a second dispersant, 0.1-0.5 wt% of a surfactant, and the balance water;
[0014] Wherein: the precious metal salt is palladium salt, platinum salt, gold salt or silver salt; the third solvent is at least one of ethyl lactate, ethyl acetate and ethylene glycol; the second dispersant is selected from at least one of polyvinyl pyrrolidone, N-methyl pyrrolidone, polyvinyl alcohol, Lubrizol solsperse46000, solsperse20000, solsperse27000 and solsperse44000; the surfactant is selected from FC-4432, FC-4430, FC-6840, FC-8730 or Chemours FS-3000 from 3M Company.
[0015] Furthermore, a composite cured coating: the preparation method of the catalyst dispersion comprises the following steps:
[0016] (1) weighing the noble metal salt according to a ratio and dissolving it in the third solvent to obtain a noble metal salt solution;
[0017] (2) weighing the second dispersant according to the ratio and adding it to the noble metal salt solution, stirring at a rate of 400 to 600 rpm for 4 to 8 hours to obtain a dispersion;
[0018] (3) filtering the dispersion, heating the filtrate under reflux at 110-130° C. for 1-3 hours, cooling, and then continuing to filter;
[0019] (4) Adding water and the surfactant to the filtrate and stirring at a rate of 400 to 600 rpm for 1 to 3 hours, and then filtering again to obtain a catalyst dispersion.
[0020] Furthermore, a composite curing coating: the catalyst ink includes the following components in mass fraction: 5.0-10.0 wt% of precious metal nanoparticles, 25.0-35.0 wt% of a third dispersant, 25.0-35.0 wt% of a fourth solvent and 25.0-35.0 wt% of a thickener; the third dispersant is selected from any one of polyvinyl pyrrolidone, solsperse46000, solsperse20000, solsperse27000 and solsperse44000; the fourth solvent is selected from one or more of ethylene glycol, glycerol, propylene glycol monomethyl ether and terpineol; the thickener is selected from one or more of ethyl cellulose, methyl cellulose, hydroxyethyl cellulose and resin.
[0021] Furthermore, a composite cured coating: the second liquid is obtained by dissolving a metal salt, a complexing agent, a reducing agent, a pH adjuster and a stabilizer in water, and the concentration of each component in the second liquid is: metal salt 10.0~15.0g / L, complexing agent 50.0~100.0ml / L, reducing agent 5.0~15.0g / L, pH adjuster 10.0~15.0g / L, stabilizer 2.0~5.0ml / L.
[0022] Furthermore, a composite curing coating: the complexing agent is selected from EDTA and / or sodium tartrate; the reducing agent is selected from formaldehyde; and the pH regulator is selected from sodium hydroxide and / or sodium carbonate.
[0023] Specifically, the metal salt can be any metal salt, preferably a transition metal salt, such as a metal salt of copper, nickel, silver, gold, cobalt, etc. This application takes copper salt as an example, which can be selected from any one of copper sulfate, copper chloride, copper nitrate, and copper phosphate.
[0024] The present invention also provides a method for preparing a composite cured coating, which comprises the following steps in sequence:
[0025] S1, applying the first liquid to the surface of the substrate, and then drying at 50-90° C. for 2-10 minutes to obtain a first solidified layer;
[0026] Wherein: the coating method can be roller coating, slit coating, spin coating, etc., and the substrate can be selected from polyethylene terephthalate (PET), polyethylene naphthalate (PEN), cellulose acetate (TAC), alicyclic hydrocarbons (COP), polymethyl methacrylate (PMMA), polyimide (PI), biaxially oriented polypropylene (BOPP), polypropylene (PP), polycarbonate, copolymers, blends or combinations thereof and other flexible substrates;
[0027] S2. Applying the catalyst precursor liquid, catalyst dispersion or catalyst ink to the surface of the first solidified layer and baking at 60-90° C. for 2-4 minutes, then continuing to bake or UV curing to form a catalytic layer, at which time the first solidified layer undergoes a cross-linking polymerization reaction (the catalytic layer does not participate in the cross-linking reaction), and the catalytic layer and the first solidified layer together form a cured catalytic layer; wherein: the coating method in step S2 is inkjet printing, spin coating, roller coating, dip coating, etc.;
[0028] S3. Immerse the substrate in a second liquid at 35-42° C. for 6-10 minutes to form a second solidified layer deposited on the surface of the catalytic layer.
[0029] Beneficial effects of the present invention:
[0030] (1) The first solidified layer of the present invention is formed by solidifying the first liquid on the surface of the substrate. The present invention optimizes the formulation of the first liquid, wherein a polymer containing at least three cross-linkable functional groups (such as trifunctional acrylate, tetrafunctional acrylate, and hexafunctional acrylate) is selected. The cross-linking degree of the polymer generated by using these materials is higher than that of the polymer generated by low-functionality materials, thereby obtaining a first solidified layer with higher adhesion to the substrate and higher strength. However, the brittleness of such a solidified layer is high and should be avoided. Therefore, the present invention optimizes the ratio design so that the proportion of trifunctional acrylate does not exceed 45wt%, the proportion of tetrafunctional acrylate does not exceed 25wt%, and the proportion of hexafunctional acrylate does not exceed 10wt%. At the same time, the first liquid is obtained by combining with other components. Finally, a first solidified layer with high adhesion to the substrate and high strength and low brittleness is obtained, which solves the problem of high brittleness.
[0031] (2) The composite cured coating of the present invention has good bending properties, can be cured by light or heat radiation to form a specific pattern, and can form a conductive layer and a conductive pattern. DETAILED DESCRIPTION
[0032] The technical solutions of the present invention will be clearly and completely described below in conjunction with specific embodiments. Obviously, the embodiments described are only some embodiments of the present invention, rather than all embodiments. The following description of at least one exemplary embodiment is actually only illustrative and is in no way intended to limit the present invention and its application or use. All other embodiments obtained by ordinary technicians in this field based on the embodiments of the present invention without making any creative work are within the scope of protection of the present invention.
[0033] Example 1
[0034] Provided is a composite cured coating, comprising a first cured layer, a catalytic layer, and a conductive second cured layer sequentially stacked on a surface of a substrate;
[0035] The first solidified layer is formed by coating a first liquid on the surface of the substrate and solidifying the first liquid, and the first liquid comprises the following components by mass fraction: 20.0 wt% of methyl acrylate (acrylate monomer), 25.0 wt% of a low-functionality polymer (including 25.0 wt% of dipropylene glycol diacrylate and 10.0 wt% of ditrimethylolpropane tetraacrylate), 3.0 wt% of Irgacure 184 (UV initiator), and 42.0 wt% of cyclopentanone (first solvent);
[0036] The catalytic layer is formed by coating a catalyst precursor liquid on the first solidified layer and solidifying it, and the catalyst precursor liquid includes the following components by mass fraction: 7.0 wt% of palladium acetate (precious metal salt), 8.0 wt% of polyvinyl pyrrolidone (first dispersant) and 85.0 wt% of ethyl acetate (second solvent); the preparation process of the catalyst precursor liquid is as follows: (1) dissolving palladium acetate in ethyl acetate to obtain a palladium solution; (2) adding polyvinyl pyrrolidone to the palladium solution and stirring at a speed of 550 rpm for 8 hours to obtain a catalyst precursor liquid;
[0037] The second solidified layer is formed by forming a second liquid on the catalytic layer. The second liquid is obtained by dissolving copper sulfate (metal salt), EDTA (complexing agent), formaldehyde (reducing agent), sodium hydroxide (pH regulator) and a stabilizer for maintaining the stability of the second liquid and ensuring the quality of the second solidified layer in water. The concentrations of the components in the second liquid are: copper sulfate 12.5 g / L, complexing agent 60.0 ml / L, formaldehyde 10.0 g / L, pH regulator 12.0 g / L, and stabilizer 2.2 ml / L.
[0038] Example 2
[0039] Provided is a composite cured coating, comprising a first cured layer, a catalytic layer, and a conductive second cured layer sequentially stacked on a surface of a substrate;
[0040] The first solidified layer is formed by coating a first liquid on the surface of the substrate and solidifying the first liquid, and the first liquid comprises the following components by weight: 15.0 wt% of 2-ethyl acrylate (acrylate monomer), a low-functionality polymer (including 15.0 wt% of ethoxylated trihydroxypropane triacrylate and 5.0 wt% of dipentaerythritol hexaacrylate), 5.0 wt% of AIBN (initiator), and 60.0 wt% of acetone (first solvent);
[0041] The catalytic layer is formed by coating a catalyst dispersion on the first solidified layer and solidifying the catalyst dispersion, and the catalyst dispersion comprises the following components by mass fraction: 0.3 wt% of palladium acetate (noble metal salt), 12.0 wt% of ethyl lactate (third solvent), 3.5 wt% of Lubrizol solsperse 46000 (second dispersant), 0.2 wt% of FC-4432 (surfactant) and the balance of water (84.0 wt%); the preparation method of the catalyst dispersion comprises the following steps: (1) weighing palladium acetate according to the ratio and mixing it; (1) dissolving the catalyst in ethyl lactate to obtain a noble metal salt solution; (2) weighing a second dispersant according to the ratio and adding it to the noble metal salt solution and stirring at a rate of 550 rpm for 6 hours to obtain a dispersion; (3) filtering the dispersion with a 1.0 μm glass fiber filter paper, heating the filtrate to reflux at 120°C for 3 hours, cooling it to room temperature, and then filtering it with a 1.0 μm glass fiber filter paper; (4) adding water and a surfactant to the filtrate and stirring it at a rate of 550 rpm for 1 hour, and then filtering it again with a 1.0 μm glass fiber filter paper to obtain a catalyst dispersion;
[0042] The second solidified layer is formed by forming a second liquid on the catalytic layer. The second liquid is obtained by dissolving copper chloride (metal salt), sodium tartrate (complexing agent), formaldehyde (reducing agent), sodium carbonate (pH regulator) and a stabilizer for maintaining the stability of the second liquid and ensuring the quality of the second solidified layer in water. The concentrations of the components in the second liquid are: copper chloride 15.0 g / L, complexing agent 50.0 ml / L, formaldehyde 5.0 g / L, pH regulator 10.0 g / L, and stabilizer 3.0 ml / L.
[0043] Example 3
[0044] Provided is a composite cured coating, comprising a first cured layer, a catalytic layer, and a conductive second cured layer sequentially stacked on a surface of a substrate;
[0045] The first solidified layer is formed by coating a first liquid on the surface of the substrate and solidifying the first liquid, and the first liquid comprises the following components by mass fraction: 29.0 wt% of methyl acrylate (acrylate monomer), 10.0 wt% of a low-functionality polymer (including 10.0 wt% of trimethylolpropane triacrylate and 10.0 wt% of ethoxylated pentaerythritol tetraacrylate), 1.0 wt% of lauroyl peroxide (initiator), and 50.0 wt% of ethyl acetate (first solvent);
[0046] The catalytic layer is formed by coating a catalyst ink on the first solidified layer and solidifying the catalyst ink, and the catalyst ink comprises the following components by mass fraction: 7.0 wt% of silver nanoparticles, 31.0 wt% of polyvinyl pyrrolidone (third dispersant), 31.0 wt% of ethylene glycol (fourth solvent), and 31.0 wt% of hydroxyethyl cellulose (viscosity agent); the preparation method of the catalyst ink comprises: (1) mixing the third dispersant, the fourth solvent, and the viscosity agent in proportion and stirring for 1.5 hours to form a dispersion system; (2) adding the silver nanoparticles to the dispersion system and continuing to stir for 12 hours to obtain the catalyst ink;
[0047] The second solidified layer is formed by forming a second liquid on the catalytic layer. The second liquid is obtained by dissolving copper phosphate (metal salt), EDTA (complexing agent), formaldehyde (reducing agent), sodium carbonate (pH regulator) and a stabilizer for maintaining the stability of the second liquid and ensuring the quality of the second solidified layer in water. The concentrations of the components in the second liquid are: 10.0 g / L of copper chloride, 80.0 ml / L of complexing agent, 15.0 g / L of formaldehyde, 15.0 g / L of pH regulator, and 5.0 ml / L of stabilizer.
[0048] Example 4
[0049] A method for preparing a composite cured coating is provided, the method comprising the following steps in sequence:
[0050] S1. The first liquid in Example 1 is applied to the surface of polyethylene terephthalate (PET, substrate) by roller coating, and then dried in an oven at 70° C. for 5 minutes to obtain a first solidified layer;
[0051] S2. The catalyst precursor liquid of Example 1 is applied to the surface of the first solidified layer by roller coating and dried in an oven at 70° C. for 3 minutes, followed by UV curing to form a catalytic layer. At this time, the first solidified layer undergoes a cross-linking polymerization reaction (the catalytic layer does not participate in the cross-linking reaction), and the catalytic layer and the first solidified layer together form a cured catalytic layer;
[0052] S3. The PET substrate having the first solidified layer and the catalytic layer formed thereon is immersed in the second liquid of Example 1, specifically immersed in the second liquid at 40°C for 8 minutes. The catalyst on the surface of the catalytic layer contacts the second liquid, and the catalytic metal ions are reduced to metal elements by the reducing agent, thereby being deposited on the surface of the catalytic layer to form a second solidified layer (metal conductive layer), thereby obtaining a composite solidified coating.
[0053] The present invention optimizes the design of the components of each coating liquid so that the obtained composite cured coating has good bending performance and is not prone to brittle cracking, thereby solving the brittleness problem faced by the existing cured coating technology.
[0054] The above preferred embodiments of the present invention are only used to explain the present invention and are not used to limit the present invention. Any obvious changes or modifications derived from the technical solution of the present invention are still within the scope of protection of the present invention.
Claims
1. A composite cured coating, characterized in that: The composite cured coating comprises a first cured layer sequentially stacked on the surface of the substrate, a catalyst layer for initiating the formation of a second cured layer, and the second cured layer having a conductive effect; The first solidified layer is formed by coating a first liquid on the surface of the substrate and solidifying it, and the first liquid includes a low-functionality polymer, an initiator, and a first solvent; the catalytic layer is formed by coating a catalyst precursor liquid, a catalyst dispersion, or a catalyst ink on the first solidified layer and solidifying it; The second solidified layer is formed on the catalytic layer by a second liquid, and the second liquid is a metal complex salt solution, which includes a metal salt, a complexing agent, a reducing agent, a stabilizer, a pH regulator and water.
2. A composite cured coating according to claim 1, characterized in that: The first liquid includes the following components by mass fraction: 10.0-30.0 wt% of acrylate monomer, 20.0-45.0 wt% of low-functionality polymer, 1.0-5.0 wt% of initiator, and 40.0-60.0 wt% of first solvent; Wherein: the acrylate monomer is selected from one of methyl acrylate, ethyl acrylate, 2-methyl methacrylate, and 2-ethyl acrylate; The low-functionality polymer is selected from at least one of monofunctional acrylate, difunctional acrylate, trifunctional acrylate, tetrafunctional acrylate, and hexafunctional acrylate; the monofunctional acrylate is selected from one of isobornyl acrylate SR506D, caprolactone acrylate SR495, and lauryl acrylate SR335; the difunctional acrylate is selected from one of tripropylene glycol diacrylate, dipropylene glycol diacrylate, and polyethylene glycol 400 diacrylate; the trifunctional acrylate is selected from one of trimethylolpropane triacrylate and ethoxylated trihydroxypropane triacrylate; the tetrafunctional acrylate is selected from one of ethoxylated pentaerythritol tetraacrylate and ditrimethylolpropane tetraacrylate; and the hexafunctional acrylate is selected from dipentaerythritol hexaacrylate; The initiator is a UV photoinitiator or a thermal initiator, the UV photoinitiator is selected from one of Irgacure184, Irgacure369, Irgacure917, and Irgacure1700, and the thermal initiator is selected from one of benzoyl oxide, lauroyl peroxide, azobis-(1-hydroxycyclohexane), and AIBN; the first solvent is selected from one of acetone, cyclopentanone, cyclohexanone, ethyl lactate, and ethyl acetate.
3. A composite cured coating according to claim 2, characterized in that: The low-functional polymer is selected from at least one of trifunctional acrylate, tetrafunctional acrylate, and hexafunctional acrylate, and the trifunctional acrylate accounts for no more than 45% of the weight of the first liquid, the tetrafunctional acrylate accounts for no more than 25% of the weight of the first liquid, and the hexafunctional acrylate accounts for no more than 10% of the weight of the first liquid.
4. The composite cured coating according to claim 1, characterized in that: The catalyst precursor liquid comprises the following components by mass fraction: 5.0-10.0 wt% of a noble metal salt, 5.0-10.0 wt% of a first dispersant, and the balance a second solvent; Wherein: the noble metal salt is selected from silver salt, palladium salt, platinum salt or gold salt; the first dispersant is polyvinyl pyrrolidone and / or N-methyl pyrrolidone; the second solvent is selected from at least one of ethylene glycol, glycerol, diacetone alcohol, methoxypropanol and ethyl acetate.
5. The composite cured coating according to claim 1, characterized in that: The catalyst dispersion comprises the following components in mass fractions: 0.2-0.5 wt% of a noble metal salt, 10.0-15.0 wt% of a third solvent, 1.0-5.0 wt% of a second dispersant, 0.1-0.5 wt% of a surfactant, and the balance water; Wherein: the precious metal salt is palladium salt, platinum salt, gold salt or silver salt; the third solvent is at least one of ethyl lactate, ethyl acetate and ethylene glycol; the second dispersant is selected from at least one of polyvinyl pyrrolidone, N-methyl pyrrolidone, polyvinyl alcohol, Lubrizol solsperse46000, solsperse20000, solsperse27000 and solsperse44000; the surfactant is selected from FC-4432, FC-4430, FC-6840, FC-8730 or Chemours FS-3000 from 3M Company.
6. The composite cured coating according to claim 5, characterized in that: The preparation method of the catalyst dispersion comprises the following steps: (1) weighing the noble metal salt according to a ratio and dissolving it in the third solvent to obtain a noble metal salt solution; (2) weighing the second dispersant according to the ratio and adding it to the noble metal salt solution and stirring evenly to obtain a dispersion; (3) filtering the dispersion, heating the filtrate to reflux, cooling it, and then continuing to filter it; (4) Water and the surfactant are added to the filtrate and stirred, and then filtered again to obtain a catalyst dispersion.
7. The composite cured coating according to claim 1, characterized in that: The catalyst ink comprises the following components by mass fraction: 5.0-10.0 wt% of noble metal nanoparticles, 25.0-35.0 wt% of a third dispersant, 25.0-35.0 wt% of a fourth solvent, and 25.0-35.0 wt% of a thickener; Wherein: the third dispersant is selected from any one of polyvinyl pyrrolidone, solsperse46000, solsperse20000, solsperse27000, and solsperse44000; The fourth solvent is selected from one or more of ethylene glycol, glycerol, propylene glycol monomethyl ether, and terpineol; the thickener is selected from one or more of ethyl cellulose, methyl cellulose, hydroxyethyl cellulose, and resin.
8. The composite cured coating according to claim 1, characterized in that: The second liquid is obtained by dissolving a metal salt, a complexing agent, a reducing agent, a pH adjusting agent and a stabilizer in water, and the concentrations of the components in the second liquid are: 10.0-15.0 g / L of metal salt, 50.0-100.0 ml / L of complexing agent, 5.0-15.0 g / L of reducing agent, 10.0-15.0 g / L of pH adjusting agent, and 2.0-5.0 ml / L of stabilizer.
9. The composite cured coating according to claim 8, characterized in that: The complexing agent is selected from EDTA and / or sodium tartrate; the reducing agent is selected from formaldehyde; and the pH regulator is selected from sodium hydroxide and / or sodium carbonate.
10. The method for preparing a composite cured coating according to any one of claims 1 to 9, characterized in that: The method comprises the following steps in sequence: S1, applying the first liquid to the surface of the substrate, and then drying at 50-90° C. for 2-10 minutes to obtain a first solidified layer; S2. Applying the catalyst precursor liquid, catalyst dispersion or catalyst ink to the surface of the first solidified layer and baking at 60-90° C. for 2-4 minutes, and then continuing to bake or UV curing to form a catalyst layer; S3. Immerse the substrate in a second liquid at 35-42° C. for 6-10 minutes to form a second solidified layer deposited on the surface of the catalytic layer.